Combination of ultrasound-guided pectoral nerve block I and serratus anterior plane block for attenuation of surgical stress response during modified radical mastectomy: A prospective interventional randomized controlled trial - Monotosh Pramanik,; Shalini Chaudhuri,; Sandipan Banerjee,; Uddalak Chattopadhyay,; Syed Sadaqat Hussain,; Nikhil Kumar Singh,; Jyotirmay Kirtania, (Asian Journal of Medical Sciences, 2024)
Background: General anesthesia with multimodal analgesia is the standard anesthetic management during modified radical mastectomy. In this study, a combined ultrasound-guided pectoral nerve block (PECS I) and serratus anterior plane (SAP) block were used for surgical stress response attenuation and post-operative analgesia. Aims and Objectives: This study aimed to compare the efficacy of combined PECS I and SAP block to intravenous (IV) multimodal analgesia in attenuating surgical stress response and post-operative analgesia in patients who underwent modified radical mastectomy with axillary clearance. The primary objective was to estimate the intraoperative fentanyl requirement to reduce autonomic response due to surgical stimulus. The intraoperative vitals, post-operative numeric rating scale pain score, post-operative analgesic use in the recovery room, and incidence of post-operative nausea vomiting were the secondary objectives. Materials and Methods: Thirty-six consenting patients were randomized into two groups. After induction of general anesthesia, Group B patients received ultrasound-guided PECS I and SAP block whereas Group C patients received IV analgesics only. Intraoperative fentanyl dosage to keep the systolic blood pressure (SBP) and heart rate (HR) within 20% of baseline were noted in the both groups. Intraoperative vitals, post-operative pain score, analgesic requirement, and incidence of post-operative nausea, and vomiting were also recorded in the both groups. Results: Surgical stress response attenuation was achieved with a lower dosage of fentanyl in Group B compared to Group C (intraoperative fentanyl [mean±SD], 116.11±25.70 μg vs. 134.44±20.07 μg, P=0.023). Compared to Group C, intraoperative reduction in SBP and HR was higher in Group B (SBP reduction [mean±SD], 24.03±12.5 mm of Hg vs. 15.2±13.05 mm of Hg, P=0.045 and HR reduction [mean±SD], 18.61±6.6 beats/min vs. 10.73±10.03 beats/min, P=0.009, respectively). The apparently higher pain scores in the control group were statistically insignificant. Conclusion: A combined PECS I and SAP block attenuates intraoperative autonomic stress response due to the surgical stimulus with significantly less opioid requirement.